High resolution, week-long, locomotion time series from Japanese quail in a home-box environment - Guzmán, Diego A. (2016)
Fil: Flesia, Ana Georgina. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.